2021
DOI: 10.3390/genes12060880
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Muellerian Tumors of the Urinary Tract

Abstract: In the 2016 WHO classification of genitourinary tumors Muellerian tumors of the urinary tract (MTUT) comprise clear cell adenocarcinomas and endometrioid carcinomas. Since these rare tumors remained understudied, we aimed to characterize their molecular background by performing DNA- and RNA-based targeted panel sequencing. All tumors (n = 11) presented single nucleotide alterations (SNVs), with ARID1A mutations being the most prevalent (5/11, 45%). Besides frequent ARID1A mutations, loss of ARID1A protein is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…Our study also found persistent lack of p63 expression in CCACLUT, which may be helpful in differentiating from UCa, as p63 is strongly positive in most of the UCa [15]. The controversy on the cellular origin of CCACLUT remains despite several reports dedicated solely to address the issue [8,16]. Oliva et al [6] reported four CCACLUT with concurrent UCa, with additional five cases demonstrating "pseudostratified epithelium reminiscent of transitional epithelium", presenting as supporting evidence of the urothelial origin of CCACLUT.…”
Section: Discussionsupporting
confidence: 56%
“…Our study also found persistent lack of p63 expression in CCACLUT, which may be helpful in differentiating from UCa, as p63 is strongly positive in most of the UCa [15]. The controversy on the cellular origin of CCACLUT remains despite several reports dedicated solely to address the issue [8,16]. Oliva et al [6] reported four CCACLUT with concurrent UCa, with additional five cases demonstrating "pseudostratified epithelium reminiscent of transitional epithelium", presenting as supporting evidence of the urothelial origin of CCACLUT.…”
Section: Discussionsupporting
confidence: 56%
“…On comparing the identified mutation spectrum of urethral CCA to the TCGA data of endometrial, ovarian, bladder, and kidney tumors, which are differential diagnoses owing to similarities in location and histologic findings, CCA showed the highest similarity to endometrial adenocarcinoma. Genetic variants reported in previous studies, such as PIKC3CA and ARID1A [ 6 , 7 , 15 ], show a particularly high frequency in endometrial cancer, and driver genes such as CSMD3 , CHD4 , and KMT2D also show significant similarity to endometrial cancer. Although CSMD3 and ARID1A are also frequently altered in urothelial carcinoma or bladder cancer, the absence of a TERT promoter mutation, the most prevalent mutation in urothelial carcinoma [ 16 ], indicates the non-urothelial origin of urethral CCA.…”
Section: Discussionmentioning
confidence: 97%
“…In another series of four cases, recurrent pathogenic PIK3CA (p.E545K) and KRAS (p.G12D) variants (3/4), an APC (p.S2310X) variant (1/4), a TP53 (p.R273C) variant (1/4), and MYC amplification (1/4) were identified; the authors suggested that the activation of the PI3K/AKT/mTOR pathway was a possible underlying oncogenic events [ 7 ]. In recent studies, mutations in KRAS and chromatin modeling genes, such as ARID1A , ARD1B , and SMARCA4 , were reported to be common finding of female patients with genital tract CCA [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows a male predominance with a ratio M:F of 2-3 to 1. Clear cell adenocarcinoma is considered of Müllerian origin, i.e., thought to arise from preexisting Müllerian precursors within the urinary bladder and urethra, and shows a female predominance with a ratio of 1 to 4.6 [10,11].…”
Section: Adenocarcinomamentioning
confidence: 99%